2008
DOI: 10.1158/1078-0432.ccr-08-1620
|View full text |Cite
|
Sign up to set email alerts
|

Perilobar Nephrogenic Rests Are Nonobligate Molecular Genetic Precursor Lesions of Insulin-Like Growth Factor-II-Associated Wilms Tumors

Abstract: Purpose: Perilobar nephrogenic rests (PLNRs) are abnormally persistent foci of embryonal immature blastema that have been associated with dysregulation at the 11p15 locus by genetic/ epigenetic means and are thought to be precursor lesions of Wilms tumor. The precise genomic events are, however, largely unknown. Experimental Design: We used array comparative genomic hybridization to analyze a series of 50 PLNRs and 25 corresponding Wilms tumors characterized for 11p15 genetic/epigenetic alterations and insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 32 publications
2
35
1
Order By: Relevance
“…Thus, at least in the sections analyzed from these five cases, cells with 16q deletions were confined to blastemal or blastemal-anaplastic elements and in no case were they present in all of the neoplastic cells ( Figure 1H). These results are largely consistent with recently published aCGH data on microdissected material, 34 showing that 16q deletions are typically not present in perilobar nephrogenic rests adjacent to tumors with 16q deletions, suggesting that 16q deletions are late events in Wilms tumor development. Based on these collective data, we hypothesized that 16q deletions promote a block of differentiation in blastemal cells, preventing differentiation toward more mature tissue elements in favor of self-renewal of blastemal cells and histological progression toward anaplasia.…”
Section: Q Deletions Are Confined To Immature Tumor Tissue Elementssupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, at least in the sections analyzed from these five cases, cells with 16q deletions were confined to blastemal or blastemal-anaplastic elements and in no case were they present in all of the neoplastic cells ( Figure 1H). These results are largely consistent with recently published aCGH data on microdissected material, 34 showing that 16q deletions are typically not present in perilobar nephrogenic rests adjacent to tumors with 16q deletions, suggesting that 16q deletions are late events in Wilms tumor development. Based on these collective data, we hypothesized that 16q deletions promote a block of differentiation in blastemal cells, preventing differentiation toward more mature tissue elements in favor of self-renewal of blastemal cells and histological progression toward anaplasia.…”
Section: Q Deletions Are Confined To Immature Tumor Tissue Elementssupporting
confidence: 92%
“…34 Based on this, the authors suggested that 16q deletions are late events in Wilms tumorigenesis, preceded by genetic and epigenetic up-regulation of IGF2. Consistent with this, we found that 16q deletions are typically confined to blastemal components with or without anaplastic features in Wilms tumor and are rare/absent in nephrogenic rests and maturing tumor elements (stromal and epithelial).…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Other common genetic imbalances such as þ 12 and þ 1q/À16q were also not found in our cases of metanephric adenoma. [23][24][25][26] We did not observe amplification of 7q corresponding to isochromosome 7q observed in adult Wilms' tumors. 27 Despite some phenotypic overlap between metanephric adenoma and predominantly epithelial Wilms' tumor (immunoreactivity for WT-1, for example), there was no evidence to indicate any association between the two neoplasms from the molecular genetic point of view.…”
Section: Discussioncontrasting
confidence: 57%
“…Nephrogenic rests do not always develop into Wilms tumours however, and the majority of them undergo regression or involution 16 17. Genetic studies of nephrogenic rest and paired tumour tissue have previously yielded insight into the genetic events associated with progression to Wilms tumour.…”
mentioning
confidence: 99%